Structurally well-defined group 4 metal complexes as initiators for the ring-opening polymerization of lactide monomers - Sauer, Andreas; Kapelski, Andreas; Fliedel, Christophe; Dagorne, Samuel; Kol, Moshe; Okuda, Jun (Dalton transactions : an international journal of inorganic chemistry, 2013)
Polylactide (PLA) is an attractive polymeric material due to its origin from annually renewable resources and its biodegradability. The ring-opening polymerization (ROP) of lactide initiated by Lewis acidic and oxophilic metal-based catalysts constitutes the method of choice to access PLA in a controlled and stereoselective manner. The design and synthesis of ligand-supported metal complexes to act as effective ROP initiators of lactide monomers have been the subject of numerous investigations over the past decades. In view of their oxophilic nature, well-defined group 4 metal complexes supported by polydentate supporting ligands have appeared as active initiators for lactide ROP. This perspective summarizes various classes of structurally well-defined group 4 metal initiators developed for lactide ROP. It also provides observed trends regarding their catalytic performance. Whenever appropriate and possible, catalyst structureROP performance ( i.e. activity, control and stereoselectivity) relationships are rationalized. Group 4 metal complexes supported by polydentate supporting ligands have appeared as a new family of active initiators for the ring-opening polymerization (ROP) of lactide monomers. This perspective summarizes the various classes of group 4 metal initiators.